2009
DOI: 10.1016/j.jhazmat.2008.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heavy metals during composting of the tannery sludge using physicochemical and spectroscopic techniques

Abstract: The major limitation of direct application of tannery sludge compost in agriculture is the total heavy metal contents and their bioavailability to the soil-plant system. This study focused on the heavy metal characterization and the influence of changing the physicochemical properties of the medium throughout the composting on the concentrations, bioavailability or chemical forms of Cr, Cu, Zn, Pb and Cd in tannery sludge. The study shows that throughout the 60 days of composting, physicochemical analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 34 publications
1
10
0
6
Order By: Relevance
“…These data are consistent with those of Haroun et al (2009), who observed that during the sewage sludge mineralization stage there is a substantial increment of contaminants.…”
Section: Resultssupporting
confidence: 93%
“…These data are consistent with those of Haroun et al (2009), who observed that during the sewage sludge mineralization stage there is a substantial increment of contaminants.…”
Section: Resultssupporting
confidence: 93%
“…Numerous studies have been conducted all over the world in order to finally solve the problem of tannery sewage sludge and tannery waste in general. The use of methods such as co-digestion (Zupancic and Jemec, 2010) or composting (Haroun et al, 2009) is strictly dependent on chromium concentration, which represents the main limitation. As noted by Altas (2009), chrome concentration as low as 27 mg/l negatively affects methane production during co-digestion, which means that the amount of co-digested sewage sludge is limited.…”
Section: Introductionmentioning
confidence: 99%
“…A composição do estrume suíno pode variar conforme inúmeros fatores, como a alimentação dos animais, condições de coleta, períodos de armazenamento, entre outros. No caso do lodo de ETE os valores de CO e NTK são aproximados aos obtidos por outros autores, como Haroun et al (2009). Os teores de cromo encontrados na literatura são de grande divergência, que pode ocorrer de acordo com as etapas realizadas no processamento do curtume.…”
Section: Caracterização Dos Resíduosunclassified